Adaptation and integration jr rural youth result of social research on the example of Turkestan,Zhambyl,Kyzylorda regions - Tulebayeva М.; Rystina И. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
Youth is the future of the country, the driving force of society, as well as the main factor of social resistance and change, rural youth is one of the most vulnerable social groups in the country, which is quickly exposed to political and social threats. They have their own uniqueness, demand and taste, need, as well as their own path of development. There are always opportunities for talented, active and competitive urban youth, but there are difficulties in choosing a path that will help rural youth realize their potential. Therefore, it is very important to conduct research on the topic of adaptation and integration of rural youth through the mechanisms of social elevators in the southern region of the country, especially in the Almaty, Turkestan, Kyzylorda and Zhambyl regions, where young people are most concentrated. This study examines the reasons for the migration of rural youth living in the cities of Kyzylorda, Taraz, Turkestan, the difficulties of adaptation to urban life, state programs to support youth, the importance of education, politics, the army and religion in the adaptation and integration of rural youth. youth, the development of adaptation and integration of rural youth through the mechanisms of social elevator for research proposals. The article analyzes the results of a sociological study on the issues of adaptation and integration of rural youth based on a focus group discussion, taking into account the specifics of each region in the specified region.